2016
DOI: 10.1111/1753-0407.12413
|View full text |Cite
|
Sign up to set email alerts
|

Study and evaluation the impact of vitamin D receptor variants on the risk of type 2 diabetes mellitus in Han Chinese

Abstract: This study provides novel evidence that rs739837 is associated with lipid metabolism in T2DM patients. The rs739837 and rs2239179 SNPs were associated with the risk of T2DM in Han Chinese. The VDR SNPs had combined and additive effects on the risk of T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 26 publications
(28 reference statements)
0
25
1
2
Order By: Relevance
“…However, Zhang et al, showed that the BB+Bb genotype and B allele frequencies in the DM group were higher than those in the control group. In contrast to our study, other studies did not determine the role of BsmI at the rs1544410 polymorphism in T2DM [28,10] . A study by Ogunkolade et al, [30] demonstrated that the VDR variant is a significant factor in VDR mRNA and VDR expression in PBMCs and confirmed an association between VDR polymorphisms and insulin secretion capacity.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, Zhang et al, showed that the BB+Bb genotype and B allele frequencies in the DM group were higher than those in the control group. In contrast to our study, other studies did not determine the role of BsmI at the rs1544410 polymorphism in T2DM [28,10] . A study by Ogunkolade et al, [30] demonstrated that the VDR variant is a significant factor in VDR mRNA and VDR expression in PBMCs and confirmed an association between VDR polymorphisms and insulin secretion capacity.…”
Section: Discussioncontrasting
confidence: 99%
“…The vitamin D receptor (VDR) gene is located on human chromosome 12q12-q14. The genetic polymorphism involved in the development of T2DM may have multiple susceptibility SNPs [10] . Of these genes, the BsmI (rs1544410) polymorphism is within the gene intron.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D is believed to exert its effect through VDR, and genetic variations in the VDR gene lead to dysfunctional vitamin D signaling. Several studies have been executed in different populations to decipher the role of VDR polymorphisms in T2D [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] and CAD. [40][41][42][43][44][45] To the best of our knowledge, studies on the importance of vitamin D or VDR polymorphisms in T2D patients with CAD are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a drawback for this quality control method. Generally, the percentage of the retested samples is <10% . It is difficult to discover the calling error for small sample size when the error rate is low.…”
Section: Introductionmentioning
confidence: 99%